Reducing harmonics distortion using active filter / Nazlinsha Mohd Shahabuddin - Mohd Shahabuddin, Nazlinsha (2007)
Harmonic distortion in not a new phenomenon in power systems. The ac power system harmonic problems are mainly due to the substantial increase of non-linear loads due to technological advances. The connection of high power non-linear loads contributes to the generation of current and voltage harmonics components. This can lead to power quality problem if the harmonics are not reduced to acceptable level. Active filter have become a viable alternative for controlling harmonic levels in industrial and commercial facilities. In this project, technique for reducing harmonic by using shunt active filter is presented. The shunt active filter is implemented with a pulsewidth modulation (PWM) voltage source inverter. For the purpose of studying harmonics, design of single-phase and three-phase rectifier has been done. Simulation using MATLAB/Simulink has shown encouraging results.